Pengembangan Virtual Appliance Server Dengan Metode Virtualisasi - Novan Ardianto; Widyawan; Sujoko Sumaryono (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2012)
With the increasing of advanced and sophisticated computer technology currently, especially for PC and server, is marked by the appearance of dual core processor, quad core processor, even hexa core processor. Besides all applications currently, especially not 3D animation and games which utilize the maximum performance of the multicore processor, makes the advanced processor work with a low utilization rate or a little usage of this processor. The advanced processor can be used for running application and services virtually.Virtualization can be seen as a part of whole IT company trend currently. Day by day the virtualization engineering become more popular and widely used because in addition tosaving the power source, it can have a good performance at running various server services in a network. Even nowadays virtualization can run on a cluster infrastructure, which will produce HA (High Availability) server.By using applications, such as VirtualBox and Proxmox, which are very powerful tools, easily-setting and especially free, virtual appliances can be made including functions and services of a server in the real network. It aims to prove how effective and efficient the usage of the multicore processor computer is.